2021
DOI: 10.1519/jsc.0000000000003368
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Cutting Implications for Competition Outcomes in Mixed Martial Arts Cage Fighting

Abstract: Brechney, GC, Chia, E, and Moreland, AT. Weight-cutting implications for competition outcomes in mixed martial arts cage fighting. J Strength Cond Res 35(12): 3420–3424, 2021—Weight cutting is common among amateur and professional mixed martial arts (MMA) competitors because of the belief that it provides an advantage in combat sports. This study aimed to identify whether fight outcome (win vs. loss vs. type of loss) was influenced by magnitudes of body mass (BM) lost through weight cutting and BM regained bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…This result is supported by recent data from another research group who also found that MMA training load is only reduced in the week of the bout [17]. In addition to extreme 'weight cutting' seen in our cohort and MMA competitors in general [8,9], it is more likely that performance would have been impaired. Though we did not collect any direct performance data, evidence from boxing suggests that a taper of 10 days or fewer causes a reduction in combat sport performance until several days after competition [45].…”
Section: Plos Onesupporting
confidence: 89%
See 2 more Smart Citations
“…This result is supported by recent data from another research group who also found that MMA training load is only reduced in the week of the bout [17]. In addition to extreme 'weight cutting' seen in our cohort and MMA competitors in general [8,9], it is more likely that performance would have been impaired. Though we did not collect any direct performance data, evidence from boxing suggests that a taper of 10 days or fewer causes a reduction in combat sport performance until several days after competition [45].…”
Section: Plos Onesupporting
confidence: 89%
“…This apparent lack of a physiological response to solely technical training is especially relevant given that successful and unsuccessful participants may be distinguishable by their lower body force production [7]. The requirement of incorporating a multitude of potentially conflicting technical and physical focused training sessions, coupled with the requirement to "make weight" for competition [8,9], clearly highlights the challenge and importance of formulating a well-structured and periodised training plan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The athletes in Cluster 2 had a greater magnitude of total weight loss compared with those from Cluster 1 (2.8 ± 2.2 kg and 1.7 ± 1.2 kg, respectively) and a higher frequency of weight cutting throughout a competitive season (Table 2). A greater amount of weight loss would plausibly result in an increased risk of impaired physical performance [3,9,22]. However, it is unclear if such reductions in physical performance are outweighed by the benefit of competing against smaller opponents; such complications may contribute to the lack of clear benefit or detriment on performance as a result of weight cutting [1].…”
Section: Discussionmentioning
confidence: 99%
“…This study found BJJ athletes engaged in AWL/RWL less often, reduced BM by less and regained less BM post competition than those in other combat sports. Though this study shows that AWL/RWL in BJJ is not as extreme as related sports (Brechney, Chia, & Moreland, 2019), the effects of different standards of competition or time spent training or competing in BJJ were not discussed or analysed. Equally, due to the multi-national cohort used, the specific AWL/RWL characteristics of BJJ competitors in the UK cannot be directly inferred.…”
Section: Introductionmentioning
confidence: 93%